Utilization of E-Commerce as A Strategy to Increase MSME Income in Jambi Province in COVID-19 ERA - Wiralestari,; Friyani, Rita; Nurhayani, (Archives of Business Research, 2023)
Over the past two years, the whole world has been fighting the Covid-19 outbreak. Covid-19 has an impact on lifestyle changes for humans in the world. Social restrictions must be implemented for the purpose of reducing the outbreak of the epidemic. The impact of social restrictions has a negative impact on micro, small and medium enterprises (MSMEs) which experience a decrease in income until they experience bankruptcy. For this reason, MSMEs need a strategy to increase income during the Covid-19 period. E-commerce is the right strategy used by MSMEs to increase income so that MSMEs can survive in the Covid-19 era.